2015
DOI: 10.1152/ajpheart.00521.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension overrides the protective effect of female hormones on the development of aortic aneurysm secondary to Alk5 deficiency via ERK activation

Abstract: The prevalence of aortic aneurysm is five times higher in men than women among the general population. Similar sexual dimorphism also exists in syndromic aortic aneurysms triggered by TGF-β signaling disorders. To understand the responsible mechanisms, we developed an animal model where inducible deletion of the type I TGF-β receptor, Alk5, specifically in smooth muscle cells ( Alk5 iko) causes spontaneous aortic aneurysm formation. This model recapitulated an extreme scenario of the dimorphism in aortic aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…As aforementioned, the mice enrolled in the current study also carried an R26R reporter and were homozygous for the floxed Tgfbr1 allele. We have previously shown that acute loss of SMC Tgfbr1 causes thoracic aortic aneurysms and dissections (Schmit et al, ; Yang et al, b). These genetic modifications allowed us to evaluate the Cre activity in arterial SMCs.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…As aforementioned, the mice enrolled in the current study also carried an R26R reporter and were homozygous for the floxed Tgfbr1 allele. We have previously shown that acute loss of SMC Tgfbr1 causes thoracic aortic aneurysms and dissections (Schmit et al, ; Yang et al, b). These genetic modifications allowed us to evaluate the Cre activity in arterial SMCs.…”
Section: Resultsmentioning
confidence: 97%
“…We treated homozygous ( n = 3) and heterozygous ( n = 4) female mice with five consecutive doses of tamoxifen and collected the aortas 13 days after the first doses of tamoxifen injection. Evans Blue was injected intravenously 30 min prior to tissue collection to assist visualization of early stage aortopathy (Schmit et al, ; Yang et al, b). Consistent with the evaluation at d5 and d5/5, X‐gal staining of X/X Cre+ ATAs remained mosaic (53%) in medial SMCs at d13.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher PP increases shear stress and aortic wall stress, thereby increasing risk for aneurysm expansion,49 likely mediated through nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kβ) and mitogen-activated protein kinase (MAPK) pathways50—pathways that underlie cell survival/apoptosis and are regulated by DAB2IP. 51 Previous studies found significant apoptosis in the stiffened aortic segment located within AAA52 and a greater impact of activation of MAPK pathway on aneurysm expansion in hypertensive female versus male mice 53. Aortic wall tension54 and rupture rates of AAA2 are greater in women than men.…”
Section: Discussionmentioning
confidence: 97%